Human Resource Accounting System in Selected Indian Companies - Joshi, Upasna (Journal of Social and Development Sciences, 2012)
The human resource may be seen as the most fundamental of all available resources to an economy or an organization. Human resources are energies, skills, talents and knowledge of people that are or can be potentially applied to the production of goods and services. Corporations cannot run by machines or systems alone, however smart those may be. The human element in it is inevitable, even for knowledge based lean organizations of the 21st century. It is an irony that valuation of this important asset is not reflected in the books of accounts. However to enhance goodwill and attract investors, need is being felt for human resource accounting. In our present paper, an attempt has been made to do the comparative study of the human resource accounting practices of CCI, HPCL, Infosys and Rolta India Limited. The variables that are important for the purpose of human resource accounting are identified and by analyzing, the annual reports of these selected companies scores are assigned to the organizations and mean scores for these organizations were calculated. Ranks to the organizations are also given based upon the extent of the HRA information reported in their annual reports.